2012
DOI: 10.1002/cbic.201200038
|View full text |Cite
|
Sign up to set email alerts
|

Cytoskeletal Protein Expression and its Association within the Hydrophobic Membrane of Artificial Cell Models

Abstract: We demonstrate the cell‐free expression of the actin‐like protein MreB and observed its preference to localize and aggregate at the membrane interface of a water‐in‐oil‐in‐water droplet as happens in vivo. These monodisperse microdroplets were produced on a large scale using microfluidics. We suggest a possible use of this platform for theory validation in fundamental biological studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…Lipid-free experiments performed with water/oil/water (w/o/w) double emulsions (Martino et al 2012a), and water/oil (w/o) droplets (Chanasakulniyom et al 2012), showed that a freshly synthesised fusion protein, comprised of MreB joined to red fluorescent protein (RFP), accumulated at the surfactant-based emulsion interface.…”
Section: Downloaded By [University College London] At 07:47 24 June mentioning
confidence: 99%
See 1 more Smart Citation
“…Lipid-free experiments performed with water/oil/water (w/o/w) double emulsions (Martino et al 2012a), and water/oil (w/o) droplets (Chanasakulniyom et al 2012), showed that a freshly synthesised fusion protein, comprised of MreB joined to red fluorescent protein (RFP), accumulated at the surfactant-based emulsion interface.…”
Section: Downloaded By [University College London] At 07:47 24 June mentioning
confidence: 99%
“…When MreB-RFP protein was synthesised inside microfluidic-produced polymersomes, its distribution was partially on the membrane, partially localised in the polymersome core (Martino et al 2012a).…”
Section: Downloaded By [University College London] At 07:47 24 June mentioning
confidence: 99%
“…[5][6][7][8] Methods involved with combining microdroplet technologies with synthetic biology techniques have proved particularly challenging and innovative. [9][10][11][12][13][14][15][16][17] Customised DNA templates and commercially available cell-free expression systems have been combined and encapsulated in microdroplets for the synthesis of enzyme and water soluble proteins, such as green fluorescent protein (GFP) and red shifted GFP (rsGFP) . [13][14][15][16][17] Developments in synthetic biology have potential applications in the construction of artificial cells and more broadly in the production of synthetically created biological structures in artificial environments, like single-emulsion droplets.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] These studies establish a solid foundation for the engineering of more complex cellular nanosystems. In fact, it is now possible to combine individual biomimetic components to create multifunctional cellular systems that mimic functions of natural cells, including gene expression, [10][11][12][13][14] membrane transport, 14 and subcellular localization. 15 Specifically, scientists have synthesized artificial cells (or protocells) by integrating synthetic gene circuits and bio-membranes.…”
mentioning
confidence: 99%